Perceptions of harm: Verbal versus physical abuse in stalking scenarios - Sheridan, Lorraine; Scott, A. (2010)
Three studies employing student and community samples in the United Kingdom (total N = 514) explored the effects of verbal versus physical abuse upon judgments of seriousness, responsibility, and consequences in stalking scenarios. The first study manipulated verbal and physical abuse, the second manipulated presence and type of verbal threat, and the third manipulated physical injury. The findings confirmed that situational factors are at least as important an influence on judgments of stalking cases as are individual factors and that physical abuse was preeminent in decision making. Gender was also examined, and previous findings that female stalkers are wrongly perceived as less dangerous were again supported. It was concluded that because stalking is by nature diffuse, observers are readily influenced by what is most tangible in a stalking case. © 2010 International Association for Correctional and Forensic Psychology.